Citric Acid-Treated Zeolite Y (CY)/Zeolite Beta Composites as Supports for Vacuum Gas Oil Hydrocracking Catalysts: High Yield Production of Highly-Aromatic Heavy Naphtha and Low-BMCI Value Tail Oil - Wei, Qiang; Zhang, Jiarui; Liu, Xiaodong; Zhang, Pengfei; Wang, Shuqin; Wang, Yan; Zhang, Zhenli; Zhang, Tao; Zhou, Yasong (Frontiers in Chemistry, 2019)
Citric acid-treated zeolite Y (CY) and zeolite beta were mechanically mixed to obtain composite zeolites (CY-Beta) with various zeolite beta contents. The composite zeolites were used as the acid components of hydrocracking catalyst supports. The physical and chemical properties of the supports and catalysts were analyzed by N2 absorption-desorption, XRD, SEM, and NH3-TPD. The mechanical mixing of CY and zeolite beta does not destroy the textual properties of the original zeolites. However, the acidity of the composite zeolite does not fit the linearly calculated value of the two zeolites because some of the acid sites are covered or reacted with other acid sites during the mixing process. In addition, weak acid sites favor the high yield of tail oil with low BMCI value. Compared with the CY-based and beta-based catalysts, the conversion and light oil yield of the CY-Beta-based catalyst was increased. The conversion, light oil yield, and petrochemical yield of the Ni-W/20CY-Beta(20)/ASA catalyst are 78.15%, 65.0%, and 83.7%, respectively. The BMCI value of the tail oil is 4.7, and the aromatic potential content (APC) of heavy naphtha (boiling point 65-177°C) is 42%. The 1500 h pilot plant test of Ni-W/20CY-Beta(20)/ASA at 350 °C, 7.0 MPa, 2.0 h−1 LHSV, and 800 H2/oil (v/v) shows that the activity remains stable during the 1500 h evaluation. The heavy naphtha (APC about 41.0) yield of 41.2 illustrates that the catalyst has the ability to aromatize and cyclize the light fractions. The yield of diesel is about 25% with a cetane index (CI) of 59.2; the frozen point is lower than −45 °C, and the cold filter plugging point is −35 °C, demonstrating the isomerization performance for middle distillations. The yield of tail oil is 14.9% with a BMCI of 4.4, showing the high hydrogenation performance of the catalyst to transform the un-cracked tail oil to saturated hydrocarbon in order to reduce the BMCI value.